2016
DOI: 10.1038/nm.4158
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a major epitope by anti-interferon-γ autoantibodies in patients with mycobacterial disease

Abstract: The binding of autoantibodies (autoAbs) to interferon (IFN)-γ in people with mycobacterial diseases has become an emerging medical concern. Many patients display specific human leukocyte antigen (HLA) class II haplotypes, which suggests that a common T cell-dependent and B cell-dependent mechanism might underlie the production of specific anti-IFN-γ autoAbs. We show here that these autoAbs target a major epitope (amino acids 121-131, designated position (P)121-131) in a region crucial for IFN-γ receptor (IFN-γ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
100
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(106 citation statements)
references
References 46 publications
5
100
0
1
Order By: Relevance
“…Our previous study showed that NK cells can directly kill M. tuberculosis and M. kansasii by releasing the cytolytic proteins perforin and granulysin (36). We also reported that anti-IFN-g autoantibodies associated with specific MHC haplotypes play a crucial role in patients with mycobacterial infection (37). In the current study, we characterized the role of NK cells and IFN-g during early stages of M. kansasii infection in the lungs.…”
mentioning
confidence: 74%
“…Our previous study showed that NK cells can directly kill M. tuberculosis and M. kansasii by releasing the cytolytic proteins perforin and granulysin (36). We also reported that anti-IFN-g autoantibodies associated with specific MHC haplotypes play a crucial role in patients with mycobacterial infection (37). In the current study, we characterized the role of NK cells and IFN-g during early stages of M. kansasii infection in the lungs.…”
mentioning
confidence: 74%
“…This epitope displays a high degree of sequence homology to the Aspergillus Noc2 protein. It was postulated that in the warm and humid environment of Southeast Asia where exposure to Aspergillus species is common in everyday life, some individuals might develop anti-IFN-γ autoantibodies due to molecular mimicry (198). The co-evolution of anti-IFN-γ autoantibody production as the susceptibility trait amongst Southeast Asians, and the high prevalence of T. marneffei , NTM, and mellioidosis in this region is a unique combination not observed in the rest of the world, and it is so interesting that exposure to a common environmental fungal agent could indirectly induce susceptibility to other pathogens.…”
Section: Protective Immunity Against Endemic Mycoses Conferred By Cytmentioning
confidence: 99%
“…Other fungi such as Blastomyces dermatitidis and some Aspergillus spp. have developed mechanisms to mimic mammalian regulatory molecules and suppress host immunity 129,130 . The skin and the mucosal surfaces of animals and humans are rich on nutrients and provide temperate environment for commensal fungal symbionts to thrive.…”
Section: Introductionmentioning
confidence: 99%